Pengaruh Gender dan Religiusitas terhadap Penggelapan Pajak - Rahmadani, Sintia; Sari, Vita Fitria (Wahana Riset Akuntansi, 2023)
AbstractPurpose – This research aims to examine the influence of gender differences and religiosity on tax evasion. The large number of cases of tax evasion that still occur today, causing huge losses to the state, has made researchers interested in researching more deeply and developing previous research. This research is different from previous research in that previous research tended to focus on economic and legal aspects, and few studied non-economic aspects of tax evasion. This research will examine tax evasion behavior more deeply from the perspective of intrinsic factors and focus on a social-psychological perspective, namely gender and religiosity. Design/methodology/approach – This research was designed as quasi-experimental research using a quantitative approach. This research took samples from Bachelor of Accounting students from Padang State University, Andalas University and Bung Hatta University. Findings – The findings from this research are that there is a gender influence on tax avoidance behavior, where men are more likely to engage in tax avoidance than women. Religiosity also influences tax avoidance behavior. Individuals with low religiosity tend to avoid taxes compared to those with high religiosity. There is an interaction effect of gender and religiosity on tax evasion behavior, where men with high religiosity are more likely to commit tax evasion than women.Originality/value – This research is different from previous research in that previous research tended to focus on economic and legal aspects, while few studied non-economic aspects of tax evasion. This research will examine tax evasion behavior more deeply from the perspective of intrinsic factors and focus on a social-psychological perspective, namely gender and religiosity. Researchers will test the social psychological factors of gender because gender is a social psychological factor, where gender is an interesting demographic factor and has been widely researched from various perspectives. Gender is also one of the social psychological factors that is believed to be successful in influencing someone to commit tax evasion. Apart from gender, there is also the religiosity factor, where religiosity is a social psychological factor based on attitudes and perceptions. The existence of attitudes and perceptions that justify tax evasion on moral grounds comes from the starting point of religion or religiosity. There is still a dearth of research examining the relationship between these two variables. Moreover, most investigations have mainly focused on developed countries. Only a few studies have assessed the relationship between religiosity and attitudes toward tax evasion. This religiosity research also measures the Krauss and Hamzah indicators to cover the weaknesses of the Warthington indicators used by previous researchers.Research limitations/implications – The research only focuses on three universities in the city of Padang, so it can reduce the ability to generalize the findings so that further research can expand or use a direct sample of taxpayers. The implications of this research can be seen theoretically, which can support or oppose previous research, and theoretically, it can be useful for related parties to overcome the problem of tax evasion.Keywords: gender, Islam, religiosity, tax evasionArticle Type: Research Paper